Organic Nutrients Support High Primary Production in the Bay of Bengal. Issue 12 (18th June 2019) - Sarma, V. V. S. S.; Rao, D. N.; Rajula, G. R.; Dalabehera, H. B.; Yadav, K.
Abstract: The Bay of Bengal (BoB) is known to experience low productivity but high sinking carbon fluxes to the bottom, and this paradox is attributed to mineral ballast of organic matter. We found for the first time that primary production in the BoB is higher, and it is supported by dissolved organic nitrogen (DON) and phosphorus (DOP) transported from the shelf regions through eddies. Both DON and DOP contribute up to 70–99% to the total dissolved nutrients in the waters above the thermocline. DON and DOP displayed positive relationship with primary production in the upper 25 m of water column, suggesting that organic nutrients significantly support primary producers. Primary production and export production in the BoB is comparable to that in the Arabian Sea, in contrast to the earlier belief that it has low production due to lack of inorganic nutrients caused by strong salinity stratification. Key Points: High primary production in the Bay of Bengal is supported by organic nutrients Anticyclonic eddies bring organic nutrients from coastal to offshore regions Primary production in the upper 25 m contributes to 70% of column production